Characterization of Natural Fibres and Their Polymer-based Composites - Piya, Afrina K.; Raihan, Munshi M.; Khan, Ruhul A. (Journal of Research Updates in Polymer Science, 2019)
Development of new alternative materials having the superior characteristics than traditional material has become a new buzz to the researchers. One of the achievements in this field is fibre reinforced polymer composites (FRPCs). The most fascinating aspect of FRPCs is light weight but higher strength and chemical resistance. Further to obtain a biodegradable one natural fibre are taking place of synthetic fibre in the processing of NFRPCs. Researchers have done extensive research works on NFRPCs to expand it application field. But sometimes only natural fibre reinforcement cannot fulfil the design requirement. Hybridization with synthetic fibre reinforcement can significantly improve the physical and mechanical properties despite of processing parameters. Again, nanoparticle fillers are also helpful to enhance the mechanical properties. The aim of this study is to clarify the use of different types of natural fibres as reinforcement to fabricate polymer composites and their corresponding mechanical properties for particular application which will be helpful to design NFRPCs for different application.